Combustion of poultry litter and mixture of poultry litter with woodchips in a fixed bed lab-scale batch reactor. (15th February 2021) - Katsaros, Giannis; Sommersacher, Peter; Retschitzegger, Stefan; Kienzl, Norbert; Tassou, Savvas A.; Pandey, Daya Shankar
Highlights: NH3 and NO are the main N gaseous species during PL combustion. High presence of aerosols is estimated during PL combustion. Corrosion risk resulting from aerosols condensation and ash deposition. High ash melting temperature (1335 °C) due to increased concentration of Ca in PL. LCV of PL is comparable to woody biomass (SP) on a dry basis. Abstract: Experiments have been conducted in a batch fixed bed lab-scale reactor to investigate the combustion behaviour of three different biomass fuels, poultry litter (PL), blend of PL with wood chips (PL/WC) and softwood pellets (SP). Analysis of the data gathered after completion of the test runs, provided useful insights about the thermal decomposition behaviour of the fuels, the formation of N gaseous species, the release of ash forming elements and the estimation of aerosol emissions. It was observed that the N gaseous species are mainly produced during the devolatilisation phase. Hydrogen cyanide (HCN) was the predominant compound in the case of SP combustion, whereas ammonia (NH3 ) displayed the highest concentration during the combustion of PL and blend (PL/WC). With reference to ash forming elements, the release rates of potassium (K) and sodium (Na) range between 15–50% and 20–37% respectively, whereas the release rate of sulphur (S) falls between 54–92%. Chlorine (Cl) presents very high release rate for all tested fuels acquiring values greater than 85%, showing the volatile nature of the specific compound. The maximum potential of aerosol emissions was estimated based on the calculation of ash forming elements. In particular, during PL combustion the maximum aerosol emissions were observed, 2806 mg/Nm 3 (dry flue gas, 13 vol% O2 ), mainly influenced by the release rate of K in the gas phase. Fuel indexes for the pre-evaluation of combustion related challenges such as NOx emissions, potential for aerosols formation, corrosion risk, and ash melting behaviour have also been investigated.